Polishing composition and polishing method

CN122832672APending Publication Date: 2026-09-29FUJIMI INCORPORATED
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202610373433.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2026-03-25
Publication Date
2026-09-29

AI Technical Summary

Benefits of technology

[0007]本公开的发明人等为了解决上述课题而进行了深入研究。其结果,本公开的发明人等发现,通过包含水、和氧化铝颗粒,且该氧化铝颗粒的体积基准的粒度分布具有双峰性的分布的研磨用组合物,能够解决上述课题,从而完成了本公开的发明。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to a grinding composition and a grinding method. The present disclosure provides a method capable of grinding a workpiece at a high grinding removal rate and reducing defects on the surface of the workpiece after grinding. The present disclosure is a grinding composition comprising: water and alumina particles, wherein the alumina particles have a bimodal particle size distribution based on volume.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to grinding compositions and grinding methods. Background Technology

[0002] In the semiconductor industry, planarization techniques are commonly used to improve the flatness of semiconductor substrates (such as wafers). Chemical mechanical polishing (CMP) is one of the most frequently used planarization techniques. CMP is a method that uses a polishing composition containing abrasive particles such as silicon dioxide, alumina, and cerium oxide, as well as etching inhibitors and surfactants, to planarize the surface of objects such as semiconductor substrates (the workpieces being polished).

[0003] Furthermore, substrates containing resin materials (sometimes referred to as "resin-containing substrates" in this specification) are becoming increasingly common. Consequently, the demand for polishing compositions used for polishing resin-containing substrates is gradually increasing.

[0004] For example, Japanese Patent Application Publication No. 2005-268666 (equivalent to U.S. Patent Application Publication No. 2005 / 204638) discloses a chemical mechanical polishing composition comprising alumina, a complexing agent, and an oxidizing agent. The chemical mechanical polishing composition of Japanese Patent Application Publication No. 2005-268666 (equivalent to U.S. Patent Application Publication No. 2005 / 204638) can be applied to the chemical mechanical polishing of resin layers and conductor layers containing metals. Summary of the Invention

[0005] However, according to the technology described in Japanese Patent Application Publication No. 2005-268666 (equivalent to U.S. Patent Application Publication No. 2005 / 204638), it is still insufficient to simultaneously achieve high grinding removal speed and reduce defects on the surface of the grinding object after grinding.

[0006] Therefore, the purpose of this disclosure is to provide a method that can grind a workpiece at a high grinding removal rate and reduce defects on the surface of the workpiece after grinding.

[0007] The inventors of this disclosure conducted in-depth research to solve the aforementioned problems. As a result, the inventors of this disclosure discovered that the aforementioned problems could be solved by a grinding composition containing water and alumina particles, wherein the particle size distribution of the alumina particles has a bimodal distribution based on volume, thereby completing the invention of this disclosure. Detailed Implementation

[0008] The embodiments of this disclosure are described below. The embodiments shown herein are illustrative of the technical concept of this disclosure and are not intended to limit this disclosure. Therefore, all other implementable methods, usages, and techniques that can be conceived by those skilled in the art without departing from the spirit of this disclosure are included within the scope and spirit of this disclosure, and are included within the scope of the invention described in the claims and their equivalents. The embodiments described in this specification can be combined in any way to form other embodiments.

[0009] Unless otherwise specified, the operation and physical properties shall be measured at room temperature (between 20°C and 25°C) and relative humidity between 40%RH and 50%RH.

[0010] The first embodiment of this disclosure is a grinding composition comprising water and alumina particles having a bimodal particle size distribution based on volume. The grinding composition of this embodiment, having this configuration, can grind a workpiece at a high grinding removal rate and can reduce defects (especially scratches) on the surface of the workpiece after grinding.

[0011] The following describes this disclosure in detail. It should be noted that in this specification, "grinding removal speed" is synonymous with "grinding rate" and "grinding speed".

[0012] [Object to be ground]

[0013] There are no particular limitations on the objects to be polished using the polishing compositions applicable to some embodiments of this disclosure, but those containing resin materials are preferred. Specifically, according to a preferred embodiment, the polishing compositions of this disclosure are used for polishing objects containing resin materials. The polishing compositions of this disclosure are particularly suitable for polishing substrates containing patterned structures formed from materials containing resin materials, and the technical effects of this disclosure can be fully utilized when polishing such substrates.

[0014] There are no particular limitations on the resin material contained in the object being ground. Examples include polyethylene terephthalate (PET), polybenzoxazole (PBO), polybutylene terephthalate (PBT), polyimide (PI), polyamide (PA), epoxy resin, urethane acrylate resin, unsaturated polyester resin, phenolic resin, polynorbornene resin, polyacetal (POM), polycarbonate (PC), modified polyphenylene ether (m-PPE), ultra-high molecular weight polyethylene (UHMWPE), syndiotactic polystyrene (SPS), amorphous polyarylate (PAR), polysulfone (PSF), polyethersulfone (PES), polyphenylene sulfide (PPS), polyetheretherketone (PEEK), polyetherimide (PEI), benzocyclobutene (BCB), fluoropolymers, and liquid crystal polymers (LCP). Among these, polyimide (PI), epoxy resin, urethane acrylate resin, or benzocyclobutene (BCB) are preferred. The aforementioned resin material can be used alone or in combination of two or more. According to some embodiments of this disclosure, the resin material includes polyimide (PI). By including polyimide (PI), the desired effects of this disclosure can be achieved efficiently. Through such embodiments, the desired effects of this disclosure can be achieved efficiently.

[0015] The grinding material is preferably made of a metallic material in addition to the aforementioned resin material. There are no particular limitations on the type of metallic material; examples include magnesium (Mg), aluminum (Al), titanium (Ti), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), zirconium (Zr), gold (Au), silver (Ag), platinum (Pt), iridium (Ir), bismuth (Bi), niobium (Ni), molybdenum (Mo), tin (Sn), tungsten (W), and lead (Pb). Preferably, it includes transition metals (especially elements from Groups 6, 9, and 11 of the periodic table), elements from Group 13, or elements from Group 14; more preferably, it includes elements from Group 11 or Group 14. Copper (Cu) is further preferred among the Group 11 elements, and tin (Sn) is further preferred among the Group 14 elements. The aforementioned metallic material can be a pure metallic element or an alloy composed of these elements and one or more other elements. The aforementioned metal materials can be used alone or in combination of two or more.

[0016] [Grinding Composition]

[0017] [Alumina particles]

[0018] The grinding composition according to this embodiment includes alumina particles as abrasives. The abrasives mechanically grind the workpiece, increasing the grinding removal rate. The alumina particles have sufficient hardness, thus resulting in a high improvement in the grinding removal rate. Furthermore, the alumina particles according to this disclosure have a bimodal distribution in their particle size distribution on a volume basis, enabling the grinding of the workpiece (preferably a resin material) at a high grinding removal rate and reducing surface defects (especially scratches) on the workpiece after grinding.

[0019] In this specification, the volumetric particle size distribution is represented as a graph with the X-axis showing the particle size (µm) expressed as the common logarithm to the base 10 and the Y-axis showing the volumetric frequency (%). The volumetric particle size distribution of alumina particles can be determined using dynamic light scattering, laser diffraction, laser scattering, or pinhole resistance methods. In this specification, the volumetric particle size distribution measured using a laser diffraction particle size distribution measuring device is used.

[0020] The bimodality of the volumetric particle size distribution means that the particle size distribution curve has two peaks (maximum values). In the volumetric particle size distribution of alumina particles, when the peak on the smaller particle size side is designated as the first peak and the peak closer to the larger particle size side than the first peak is designated as the second peak, the ratio of the particle size PS2 at the peak of the second peak to the particle size PS1 at the peak of the first peak (PS2 / PS1) is preferably 1.3 or more and 3 or less. From the viewpoint of obtaining the effects of this disclosure more efficiently, PS2 / PS1 is more preferably 1.6 or more and 2.4 or less, and even more preferably 1.8 or more and 2.2 or less.

[0021] The particle size PS1 at the peak of the first peak of the alumina particles is preferably 0.4 µm or more, more preferably 0.43 µm or more, and even more preferably 0.45 µm or more. Furthermore, the particle size PS1 is preferably 0.60 µm or less, more preferably 0.58 µm or less, and even more preferably 0.55 µm or less. In other words, the particle size PS1 at the peak of the first peak of the alumina particles is preferably 0.4 µm or more and 0.60 µm or less, more preferably 0.43 µm or more and 0.58 µm or less, and even more preferably 0.45 µm or more and 0.55 µm or less.

[0022] The particle size PS2 at the peak of the second peak of the alumina particles is preferably 0.80 µm or more, more preferably 0.85 µm or more, and even more preferably 0.90 µm or more. Furthermore, the particle size PS2 is preferably 1.20 µm or less, more preferably 1.15 µm or less, and even more preferably 1.10 µm or less. That is, the particle size PS2 at the peak of the second peak of the alumina particles is preferably 0.80 µm or more and 1.20 µm or less, more preferably 0.85 µm or more and 1.15 µm or less, and even more preferably 0.90 µm or more and 1.10 µm or less.

[0023] Furthermore, when the peak height of the first peak is defined as H1 and the peak height of the second peak is defined as H2, the ratio of the peak height H2 of the second peak to the peak height H1 of the first peak (H2 / H1) is preferably 0.1 or more and 1.0 or less. From the viewpoint of obtaining the effects of this disclosure more efficiently, H2 / H1 is more preferably 0.2 or more and 0.9 or less, and even more preferably 0.3 or more and 0.8 or less.

[0024] <Irregularity N and Skewness S>

[0025] The alumina particles involved in this disclosure preferably have an irregularity N as shown in the following formula (1) that satisfies the relationship in the following formula (2).

[0026]

[0027]

[0028] The anisotropy N shown in equation (1) above is a parameter representing the degree of deformation of the particle's shape relative to a sphere of the same particle size. The greater the anisotropy N is than 1, the greater the degree of deformation of the particle shape. When the anisotropy N is 1, it means that the particle is a sphere. The anisotropy N of the alumina particles involved in this embodiment is in the range of 2 or more and 8 or less, therefore the degree of deformation of the particle shape is large.

[0029] In addition, the alumina particles preferably have a skewness S as shown in the following formula (3) that satisfies the relationship in the following formula (4).

[0030]

[0031]

[0032] The skewness S shown in equation (3) above is a parameter representing the symmetry (skewness) of the particle size distribution of alumina particles. A skewness S less than 1 (S < 1) means that the particle size distribution of alumina particles is biased towards the larger particle size side, that is, there are more large-sized alumina particles. On the other hand, a skewness S greater than 1 (1 < S) ​​means that the particle size distribution of alumina particles is biased towards the smaller particle size side, that is, there are more small-sized alumina particles. A skewness S of 1 (S = 1) indicates that the particle size distribution of alumina particles is symmetrical, that is, the particle size distribution of alumina particles is log-normal. The skewness S of the alumina particles involved in this embodiment is in the range of 0.50 or more and 1.00 or less, therefore it is biased towards the larger particle size side (there are more large-sized particles), or the particle size distribution is symmetrical.

[0033] Generally, it is known that larger abrasive grains have higher removal rates. Furthermore, it is known that the removal rate increases with the degree of deformation of the abrasive grain shape and its aspect ratio. On the other hand, larger abrasive grains, irregular shapes, and / or high aspect ratios increase defects such as scratches on the surface of the workpiece after grinding. Conversely, smaller abrasive grains, while having slower removal rates, tend to improve the removal of defects such as scratches on the surface of the workpiece. Additionally, it is known that spherical particles have lower removal rates than irregularly shaped particles, but they reduce defects such as scratches on the surface of the workpiece. Thus, there is a trade-off between increased removal rate and the occurrence of defects such as scratches.

[0034] However, the inventors of this disclosure have conducted repeated studies and found that by using a grinding composition containing alumina particles that satisfy at least one of the following conditions, the grinding removal rate of the grinding object (preferably a resin material) becomes higher, and the defects on the surface of the grinding object (preferably a resin material) after grinding are further reduced. The conditions are: the irregularity N shown in formula (1) satisfies the relationship of formula (2) above, and the skewness S shown in formula (3) satisfies the relationship of formula (4) above. That is, it has been found that by using a grinding composition containing alumina particles that satisfy at least one of the following conditions, the effects of this disclosure can be further improved with high efficiency: the irregularity N shown in formula (1) satisfies the relationship of formula (2) above, and the skewness S shown in formula (3) above satisfies the relationship of formula (4) above.

[0035] (Irregularity N)

[0036] When the alumina particle irregularity N shown in formula (1) satisfies the relationship in formula (2) above, the grinding removal rate of the grinding object (preferably resin material) becomes higher, and the defects (especially scratches) on the surface of the grinding object (preferably resin material) after grinding are further reduced. The alumina particle irregularity N is more preferably 2.5 or more and 7.5 or less, and more preferably 3.0 or more and 7.0 or less.

[0037] The BET specific surface area SA of the alumina particles used in calculating the anisotropy N is based on the specific surface area determined by JIS Z8830:2013. More specifically, it can be determined by the method described in the examples.

[0038] In addition, the theoretical specific surface area SA' of alumina particles is the D used in the calculation using the aforementioned skewness S. 50 The value of is calculated using the following formula (5).

[0039]

[0040] In the above formula (5), ρ is the density of alumina particles, which is 3.95 g / cm³. 3 The value of .

[0041] (skewness S)

[0042] When the skewness S of the alumina particles shown in formula (3) satisfies the relationship in formula (4) above, the grinding removal rate of the object to be ground (preferably resin material) becomes higher, and the defects (especially scratches) on the surface of the object to be ground (preferably resin material) after grinding are further reduced. The skewness S of the alumina particles is more preferably 0.55 or more and 0.95 or less, and more preferably 0.60 or more and 0.90 or less.

[0043] The D2 and D values ​​of the alumina particles used in calculating the skewness S 50 and D 98 The particle size distribution can be determined using the methods described above, such as dynamic light scattering, laser diffraction, laser scattering, or pinhole resistance. In this specification, the particle size distribution of the volume reference measured using a laser diffraction particle size distribution measuring device uses values ​​derived from the cumulative frequency of particle sizes at 2%, 50%, and 98% of the particle size range, respectively. More specifically, the measurement can be performed using the methods described in the examples.

[0044] As long as the particle size distribution based on volume has a bimodal distribution, there are no particular restrictions on the shape of alumina particles. Examples of alumina particle shapes include triangular prisms, quadrangular prisms and other polyhedral shapes, cylindrical shapes, sack-shaped shapes with the central part of the cylinder bulging more than the ends, donut-shaped shapes penetrating the central part of the disc, plate-shaped shapes, so-called cocoon-shaped shapes with a neck in the central part, so-called associated spherical shapes with multiple particles integrated, so-called konpeito shapes with multiple protrusions on the surface, rugby ball shapes, conical shapes, frustum-shaped cones, pyramidal shapes, frustum-shaped pyramids, hemispherical shapes, needle-shaped shapes, and various other shapes.

[0045] <D 50 >

[0046] D of alumina particles 50 There are no particular restrictions. For example, the D of alumina particles... 50 Preferably, the alumina particle size is 2.0 µm or less, more preferably 1.5 µm or less, further preferably 1.3 µm or less, particularly preferably 1.0 µm or less, and most preferably 0.9 µm or less. The D-size of the alumina particles... 50 Preferably, the alumina particle size is 0.05µm or more, more preferably 0.1µm or more, further preferably 0.3µm or more, particularly preferably 0.4µm or more, and most preferably 0.5µm or more. The D-value of the alumina particles... 50 When the above range is reached, it is possible to more evenly balance the increase in the grinding removal rate of the workpiece (preferably a resin material) and the reduction of defects (especially scratches) on the surface of the workpiece after grinding. The D of alumina particles... 50 A preferred example is that the micrometer is 0.05µm or more and 2.0µm or less, more preferably 0.1µm or more and 1.5µm or less, further preferably 0.3µm or more and 1.3µm or less, particularly preferably 0.4µm or more and 1.0µm or less, and most preferably 0.5µm or more and 0.9µm or less.

[0047] <α-conversion rate>

[0048] The aforementioned alumina particles preferably contain a crystalline phase that is a transitional state during the process of becoming the α phase, such as the α phase, θ phase, δ phase, or γ phase, which are preferred crystal structures for grinding abrasive particles. More preferably, they contain the α phase or θ phase, and even more preferably, they contain the α phase. Furthermore, regarding the α phase, it is believed that there is an optimal range depending on the degree of α-phase formation.

[0049] Generally, the α-phase is considered to have the hardest crystal structure, but it is presumed that when fully sintered at high temperatures to achieve α-phase formation, the particle shape becomes rounder, and the grinding performance decreases. The α-phase concentration ratio is used as a reference to indicate the degree of α-phase content in alumina particles. Preferably, the lower limit of the α-phase concentration ratio is 50% or more. More preferably, the lower limit is 60% or more, further preferably 70% or more, even more preferably 80% or more, and particularly preferably 90% or more. Furthermore, the upper limit of the α-phase concentration ratio is preferably 100% or less. More preferably, the upper limit is 98% or less. That is, the α-phase concentration ratio of alumina particles is preferably 50% or more and 100% or less, more preferably 60% or more and 98% or less, and even more preferably 80% or more and 98% or less.

[0050] By setting the α-aggregate ratio to the above-mentioned preferred range, an increase in grinding force can be expected, that is, a further increase in the grinding removal rate of the object to be ground (preferably resin material). It should be noted that the α-aggregate ratio of alumina particles can be calculated from the integral intensity ratio of the peak corresponding to the (113) plane at 2θ = 43° ± 2°, obtained by X-ray diffraction of Cu-Kα rays in the reference material and the test sample.

[0051] <Concentration (Content)>

[0052] The concentration (content) of alumina particles in the grinding composition is not particularly limited, but relative to the total mass of the grinding composition, it is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and particularly preferably 1.5% by mass or more. As the concentration of alumina particles increases, the grinding removal rate is further improved. Furthermore, the concentration (content) of alumina particles relative to the total mass of the grinding composition is preferably 25% by mass or less, more preferably 15% by mass or less, further preferably 10% by mass or less, even more preferably less than 9% by mass, and particularly preferably less than 8% by mass. When the concentration (content) of alumina particles is within the above range, the grinding removal rate of the workpiece (preferably resin material) can be further improved. In addition, it also has the effect of further reducing the occurrence of defects such as scratches on the surface of the workpiece (preferably resin material) after grinding. A preferred example of the concentration (content) of alumina particles is that, relative to the total mass of the grinding composition, it is 0.01% by mass or more and 25% by mass or less, more preferably 0.1% by mass or more and 15% by mass or less, further preferably 0.5% by mass or more and 10% by mass or less, even more preferably 1% by mass or more and less than 9% by mass, and particularly preferably 1.5% by mass or more and 8% by mass or less.

[0053] There are no particular limitations on the manufacturing method of alumina particles with a bimodal distribution; for example, a method of mixing two types of alumina particles with different particle size distributions can be cited. There are also no particular limitations on the mixing method of alumina particles; known methods such as dry mixing and wet mixing can be appropriately used.

[0054] Furthermore, as a method for manufacturing alumina particles with a bimodal distribution, one can exemplify this method by appropriately pulverizing and / or classifying the powder obtained after calcining starting materials such as alumina precursor powder. According to this method, alumina particles with anisotropy N and skewness S satisfying the relationships of equations (2) and (4) above can also be obtained efficiently.

[0055] The alumina precursor powder can be aluminum hydroxide powder or alumina powder containing a transitional alumina phase. The aluminum hydroxide powder can be gibbsite, boehmite, pseudoboehmite, diaspore, or any combination thereof. The alumina precursor powder can contain Gamma (γ), Eta (η), Theta (θ), Chi (χ), Kappa (κ), and / or Delta (δ) phase alumina.

[0056] Alumina can be formed by calcining the aforementioned alumina precursor powder. The calcination method is not particularly limited; examples include rotary kilns, tunnel kilns, electric furnaces, muffle furnaces, lift kilns, or pusher kilns. The calcination temperature can be above 700°C and below 1600°C, and the calcination time can be above 1 hour and below 48 hours. This allows for the production of α-alumina with a suitable α-oxidation rate. There is a tendency for higher calcination temperatures to result in smaller specific surface areas.

[0057] By appropriately pulverizing and classifying the calcined alumina powder, alumina with a desired particle size distribution can be obtained. Pulverization and classification can be carried out using either wet or dry processes.

[0058] As an example of a pulverizing method, the use of a pulverizing apparatus can be cited. Commonly known pulverizing apparatuses include ball mills, bead mills, planetary mills, vibratory mills, colloid mills, conical mills, disc mills, edge mills, pulverizing mills, hammer mills, mortars, particle mills, VSI mills, Wiley mills, roller mills, spray mills, homogenizers, high-pressure homogenizers, and ultrasonic devices. In each apparatus, by changing pulverizing conditions such as pulverizing time, alumina with a desired particle size distribution can be obtained.

[0059] Examples of classification methods include filtration, sieving, air classification, water jet classification, gravimetric classification, inertial classification, and centrifugal classification. Examples of filtration methods include coarse filtration, fine filtration, ultrafiltration, and reverse osmosis. Examples of filters used in filtration include mesh filters, depth filters, and membrane filters. In filtration, the particle size distribution of the powder can be controlled by filtration time, filtration speed, and filtration precision. For example, the filtration precision can be greater than 0.1µm and less than 300µm.

[0060] By appropriately selecting and / or combining one or more of the above-mentioned calcination method, pulverization method and grading / filtration method, and controlling the respective conditions, it is possible to obtain alumina particles with bimodal characteristics (preferably alumina particles whose anisotropy N and skewness S satisfy the relationship of the above-mentioned formulas (2) and (4)).

[0061] It should be noted that commercially available products can be used as the alumina particles.

[0062] [Water]

[0063] The polishing composition according to the present disclosure comprises water. Water disperses or dissolves each component. From the viewpoint of preventing the influence of impurities on other components of the polishing composition, water with as high a purity as possible is preferably used. Specifically, ion-exchanged water (deionized water), pure water obtained by removing impurity ions with an ion exchange resin and then removing foreign substances through a filter, ultrapure water, or distilled water is preferred. In addition, for the purpose of controlling the dispersibility of other components in the polishing composition, an organic solvent or the like as a dispersion medium may be further contained.

[0064] [Other Components]

[0065] The polishing composition according to the present disclosure may further contain well-known other components such as pH adjusters, surfactants, dispersants, thickeners (viscosity modifiers), surface protective agents, wetting agents, oxidizing agents, water-soluble polymers, salts, corrosion inhibitors, preservatives, and mildewcides within a range that does not impair the effects of the present disclosure. The content of these other components may be appropriately set according to the purpose of addition. Hereinafter, pH adjusters, surfactants, dispersants, thickeners (viscosity modifiers), oxidizing agents, corrosion inhibitors, preservatives and mildewcides will be described. In addition, chelating agents will also be described.

[0066] <pH调节剂>

[0067] The polishing composition according to some embodiments of the present disclosure may further comprise a pH adjuster. The pH adjuster can contribute to adjusting the pH of the polishing composition by selecting its type and addition amount.

[0068] The pH adjuster is not particularly limited as long as it is a compound having a pH adjustment function, and well-known compounds can be used. The pH adjuster is not particularly limited as long as it has a pH adjustment function, and examples thereof include acids, alkalis, and the like.

[0069] As the acid, any type of inorganic or organic acid can be used. There are no particular limitations on inorganic acids; examples include sulfuric acid, nitric acid, boric acid, carbonic acid, hypophosphorous acid, phosphorous acid, and phosphoric acid. There are no particular limitations on organic acids; examples include formic acid, acetic acid, propionic acid, butyric acid, valeric acid, 2-methylbutyric acid, hexanoic acid, 3,3-dimethylbutyric acid, 2-ethylbutyric acid, 4-methylvaleric acid, heptanoic acid, 2-methylhexanoic acid, octanoic acid, 2-ethylhexanoic acid, benzoic acid, glycolic acid, salicylic acid, glyceric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, maleic acid, phthalic acid, malic acid, tartaric acid, citric acid, and lactic acid, as well as methanesulfonic acid, ethanesulfonic acid, and hydroxyethylsulfonic acid. Among these, organic acids are preferred, and malic acid, citric acid, and maleic acid are more preferred. It should be noted that when using inorganic acids, nitric acid, sulfuric acid, and phosphoric acid are preferred.

[0070] There are no particular limitations on what constitutes an alkali; examples include salts of alkali metals, salts of alkaline earth metals, quaternary ammonium, and ammonia.

[0071] Specific examples of alkali metals include potassium and sodium. Specific examples of alkaline earth metals include calcium and strontium. Specific examples of salts include hydroxide salts, carbonates, bicarbonates, sulfates, and acetates. Specific examples of quaternary ammonium compounds include tetramethylammonium, tetraethylammonium, tetrabutylammonium, and their hydroxides. Among these, potassium carbonate, potassium hydroxide, or ammonia are preferred as bases.

[0072] pH adjusters can be used alone or in combination of two or more.

[0073] The pH of the grinding composition involved in some embodiments of this disclosure is not particularly limited. From the viewpoint of grinding removal speed, alkalinity is preferred, preferably 7 or higher. The pH can be 8 or higher, or 9 or higher, 10 or higher, or 11 or higher. Furthermore, from the viewpoint of further improving the grinding removal speed of the workpiece (preferably resin material) and further reducing defects, the pH is preferably 14 or lower, or 13 or lower, or 12 or lower, or 11.5 or lower. For example, the pH of the grinding composition can be set in the range of 7 or higher and 14 or lower, or 7 or higher and 13 or lower, or 7 or higher and 12 or lower. Within the above range, it has the effect of more evenly balancing the improvement of the grinding removal speed of the workpiece (preferably resin material) and the reduction of defects (especially scratches). The content of the pH adjuster is not particularly limited, but it is preferably an amount that allows the pH value to be within the above-mentioned preferred range. It should be noted that the pH of the grinding composition can be measured, for example, using a pH meter.

[0074] <surfactants>

[0075] Some embodiments of this disclosure involve a grinding composition that may contain a surfactant. The surfactant contained in the grinding composition of this disclosure is at least one selected from the group consisting of anionic surfactants, cationic surfactants, amphoteric surfactants, and nonionic surfactants. Among these, nonionic surfactants are preferred as the surfactant contained in the grinding composition. One surfactant may be used alone, or two or more surfactants may be used in combination.

[0076] Examples of anionic surfactants include polyoxyethylene alkyl ether acetate, polyoxyethylene alkyl sulfate, alkyl sulfate, polyoxyethylene alkyl ether sulfate, alkyl ether sulfate, alkylbenzene sulfonic acid, alkyl phosphate, polyoxyethylene alkyl phosphate, polyoxyethylene sulfosuccinic acid, alkyl sulfosuccinic acid, alkyl naphthalene sulfonic acid, alkyl diphenyl ether disulfonic acid, and their salts.

[0077] Examples of cationic surfactants include alkyl trimethylammonium salts, alkyl dimethylammonium salts, alkyl benzyl dimethylammonium salts, and alkylamine salts.

[0078] Examples of amphoteric surfactants include alkyl betaine and alkyl amine oxides.

[0079] Examples of nonionic surfactants include polyoxyethylene alkyl ethers, sorbitan fatty acid esters, glycerol fatty acid esters, polyoxyethylene fatty acid esters, polyoxyethylene alkylamines, and alkylalkanolamides.

[0080] When the grinding composition contains a surfactant, the concentration (content) of the surfactant relative to the total mass of the grinding composition is preferably 0.01% by mass or more, more preferably 0.05% by mass or more. Furthermore, the concentration (content) of the surfactant in the grinding composition relative to the total mass of the grinding composition is preferably 3.0% by mass or less, more preferably 2.0% by mass or less. When the concentration (content) of the surfactant is within the above-mentioned range, the uniformity of grinding the workpiece is further improved.

[0081] <Dispersant / Thickener (Viscosity Modifier)>

[0082] Some embodiments of this disclosure relate to grinding compositions that may contain dispersants or thickeners (viscosity modifiers). The dispersants or thickeners function to uniformly disperse the abrasive grains (alumina particles) in the liquid, thereby enabling the abrasive grains to act efficiently on the object being ground. Furthermore, by having the dispersants or thickeners present between the abrasive grains, it is also expected that the agglomeration of the abrasive grains can be suppressed, thereby inhibiting the formation of scratches caused by aggregated abrasive grains.

[0083] Specific examples of dispersants, for colloidal substances containing fine particles, include colloidal alumina, colloidal silica, colloidal zirconium oxide, colloidal titanium dioxide, alumina sol, silica sol, zirconium oxide sol, titanium dioxide sol, fumed alumina, fumed silica, fumed zirconium oxide, and fumed titanium dioxide. Additionally, sodium phosphate, sodium hexametaphosphate, and sodium pyrophosphate, which are commonly used as dispersants, can also be used.

[0084] Specific examples of thickeners include glycols and polymers such as propylene glycol or its polymers, and ethylene glycol or its polymers. More specifically, examples of glycols include propylene glycol, ethylene glycol, dipropylene glycol, polypropylene glycol, diethylene glycol, and polyethylene glycol. Examples of polymers include sodium polyacrylate, polyvinyl alcohol, and hydroxyethyl cellulose.

[0085] Oxidizing agents

[0086] When the object to be ground contains a metallic material, the grinding composition according to some embodiments of this disclosure may include an oxidizing agent. The oxidizing agent has the function of hardening the surface of the metallic material by oxidation, and suppressing the formation of defects such as scratches. Specific examples of oxidizing agents include peroxides such as hydrogen peroxide, nitrates, iodates, periodates, hypochlorites, chlorites, chlorates, perchlorates, persulfates, dichromates, permanganates, ozonated water, silver (II) salts, iron (III) salts, etc. One oxidizing agent may be used alone, or two or more may be used in combination. Furthermore, commercially available or synthetic oxidizing agents may be used.

[0087] Corrosion Inhibitor

[0088] When the object to be ground contains a metallic material, the grinding composition according to some embodiments of this disclosure may include a corrosion inhibitor. The corrosion inhibitor serves to prevent excessive dissolution of the metallic material. Examples of corrosion inhibitors include heterocyclic compounds. The number of heterocycles in the heterocyclic compound is not particularly limited. Furthermore, the heterocyclic compound may be a monocyclic compound or a polycyclic compound having fused rings. One corrosion inhibitor may be used alone, or two or more may be used in combination. Additionally, the corrosion inhibitor may be a commercially available product or a synthetic product.

[0089] Specific examples of heterocyclic compounds that can be used as corrosion inhibitors include, for example, pyrrole compounds, pyrazole compounds, imidazole compounds, triazole compounds, tetraazole compounds, pyridine compounds, pyrazine compounds, pyridazine compounds, 4-nitrogenindine compounds, indazine compounds, indole compounds, isoindole compounds, indazole compounds, purine compounds, quinazine compounds, quinoline compounds, isoquinoline compounds, naphthidine compounds, phthalazine compounds, quinoxaline compounds, quinazoline compounds, cyclophosphine compounds, pteridine compounds, thiazole compounds, isothiazole compounds, oxazole compounds, isoxazole compounds, furazine compounds, and other nitrogen-containing heterocyclic compounds.

[0090] When the grinding composition contains a corrosion inhibitor, the concentration (content) of the corrosion inhibitor relative to the total mass of the grinding composition is preferably 0.001% by mass or more, more preferably 0.005% by mass or more, and even more preferably 0.01% by mass or more. Furthermore, the concentration (content) of the corrosion inhibitor in the grinding composition relative to the total mass of the grinding composition is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and even more preferably 0.1% by mass or less. When the concentration (content) of the corrosion inhibitor is within the above-mentioned range, the effect of preventing excessive dissolution of the grinding object containing metallic materials is further enhanced.

[0091] <Mold inhibitors, preservatives>

[0092] Some embodiments of this disclosure involve grinding compositions that may contain fungicides and preservatives. Specific examples of fungicides and preservatives include isothiazolin-based preservatives (e.g., 2-methyl-4-isothiazolin-3-one, 5-chloro-2-methyl-4-isothiazolin-3-one), parabens, phenoxyethanol, etc. These fungicides and preservatives may be used alone or in combination of two or more.

[0093] Chelating agents

[0094] When the object to be ground contains a metallic material, the grinding compositions according to some embodiments of this disclosure preferably do not contain chelating agents substantially. This suppresses the increase in scratches and dents on the surface of the metallic material caused by chelating agents in the grinding composition. Here, "the grinding composition does not contain chelating agents substantially" means that chelating agents are intentionally not added to the grinding composition. This includes not only the concept of the grinding composition being completely free of chelating agents, but also cases where the grinding composition contains 0.1% by mass or less. The concentration (content) of the chelating agent relative to the total mass of the grinding composition is more preferably 0.05% by mass or less, more preferably 0.01% by mass or less, and particularly preferably 0% by mass, i.e., completely free of chelating agents. Examples of chelating agents include aminocarboxylic acid-based chelating agents and organophosphonic acid-based chelating agents.

[0095] [Grinding removal speed]

[0096] The grinding compositions disclosed in some embodiments can increase the grinding removal rate of resin materials. For example, the grinding removal rate of the resin material is preferably 0.8 µm / min or more, more preferably 1.0 µm / min or more, and even more preferably 1.1 µm / min or more. It should be noted that the grinding removal rate is determined by the method described in the examples.

[0097] [Method for manufacturing the grinding composition]

[0098] In some embodiments of the grinding compositions disclosed herein, the manufacturing method (preparation method) of the grinding composition is not particularly limited. For example, a manufacturing method including stirring and mixing alumina particles, water, and other components as needed can be appropriately employed. It should be noted that the alumina particles, water, and other components are the same as those described above, and therefore their description is omitted here.

[0099] In the grinding composition, there are no particular limitations on the temperature at which the components are mixed, but it is preferably 10°C or higher and 40°C or lower. Heating can be used to increase the dissolution rate. In addition, there are no particular limitations on the mixing time.

[0100] [Grinding Method]

[0101] The second embodiment of this disclosure relates to a grinding method comprising a step of grinding a workpiece using the above-described grinding composition. The preferred example of the workpiece to be ground in this embodiment is the same as the example listed in the description of [workpiece to be ground].

[0102] When grinding an object using an abrasive composition, the apparatus and conditions typically used in grinding can be employed. Examples of typical grinding apparatuses include single-sided grinding apparatuses and double-sided grinding apparatuses. A single-sided grinding apparatus typically uses a holder called a carrier to hold the object, supplies the abrasive composition from above, and presses a plate with an abrasive pad attached to one side of the object while rotating it, thereby grinding that side of the object. A double-sided grinding apparatus typically uses a holder called a carrier to hold the object, supplies the abrasive composition from above, and presses a plate with an abrasive pad attached to opposite sides of the object, rotating them in opposite directions, thereby grinding both sides of the object. In this case, grinding is performed based on the physical action of friction between the abrasive pad and the object, and the chemical action of the abrasive composition on the object. The abrasive pad can be made of porous materials such as non-woven fabric, polyurethane, or suede without particular limitation. It is preferable to process the abrasive pad to accumulate abrasive fluid.

[0103] Examples of grinding conditions include grinding load, plate rotation speed, carrier rotation speed, flow rate of the grinding composition, and grinding time. These grinding conditions are not particularly limited; for example, regarding the grinding load, it is preferably 0.1 psi (0.69 kPa) or more and 10 psi (69 kPa) or less, more preferably 0.5 psi (3.5 kPa) or more and 8.0 psi (55 kPa) or less. Generally, the higher the load, the higher the friction of the abrasive grains, the higher the machining force, and therefore the higher the grinding removal rate. Within this range, a sufficient grinding removal rate can be achieved, suppressing defects such as breakage of the workpiece and surface scratches caused by the load. The plate rotation speed and carrier rotation speed are preferably 10 rpm (0.17 s). -1 ) or higher and 500rpm (8.3s) -1 The following applies. The supply amount of the abrasive composition is sufficient to cover the entire object being abraded (flow rate), and can be adjusted according to conditions such as the size of the object. There are no particular restrictions on the method of supplying the abrasive composition to the abrasive pad; for example, a continuous supply method using a pump can be employed. Furthermore, the processing time is not particularly limited as long as the desired processing result can be obtained, but due to the high abrasive removal rate, a shorter time is preferable.

[0104] Furthermore, the third embodiment of this disclosure relates to a method for manufacturing a polished object, which includes a step of polishing the object using the aforementioned polishing method. The preferred example of the polished object involved in this method is the same as the example listed in the description of [polished object]. As a preferred example, a method for manufacturing an electronic circuit board including polishing a polished object containing a resin material using the aforementioned polishing method can be cited.

[0105] While embodiments of the present disclosure have been described in detail, they are merely illustrative and exemplary and not restrictive, and it is clear that the scope of the disclosure should be interpreted through the appended claims.

[0106] This disclosure includes the following forms and methods:

[0107] [1] A grinding composition comprising: water and alumina particles, wherein the alumina particles have a bimodal particle size distribution on a volume basis.

[0108] [2] According to the grinding composition described in [1] above, wherein, in the particle size distribution based on the volume of the alumina particles,

[0109] The peak on the smaller particle size side is set as the first peak.

[0110] When the peak that is closer to the larger particle size side than the first peak is designated as the second peak...

[0111] The ratio of the particle size PS2 at the peak of the second peak to the particle size PS1 at the peak of the first peak, PS2 / PS1, is greater than 1.3 and less than 3.

[0112] [3] According to the grinding composition described in [2] above, wherein the peak height of the first peak is set to H1.

[0113] When the peak height of the second peak is set to H2,

[0114] The ratio H2 / H1 of the peak height of the second peak to the peak height of the first peak is greater than 0.1 and less than 1.0.

[0115] [4] The grinding composition according to any one of [1] to [3] above, wherein the BET specific surface area of ​​the alumina particles is set as SA.

[0116] The particle size distribution based on volume of the alumina particles, with the cumulative frequency from the smallest particle size side being 50% of the particle size, is defined as D. 50 , will be by the D 50 When the calculated theoretical specific surface area is set as SA',

[0117] The irregularity N shown in equation (1) satisfies the relationship in equation (2).

[0118]

[0119]

[0120] [5] According to the grinding composition described in [4] above, wherein, in the particle size distribution based on the volume of the alumina particles,

[0121] Let the cumulative frequency from the smallest particle size side be 2% of the particle size, and set that as D2.

[0122] Let the particle size from the smallest particle size side, where the cumulative frequency is 98%, be defined as D. 98 hour,

[0123] The skewness S shown in equation (3) below satisfies the relationship in equation (4) below.

[0124]

[0125] .

[0126] [6] According to the grinding composition described in [4] or [5] above, wherein the D of the alumina particles is... 50 It is above 0.50µm and below 0.90µm.

[0127] [7] The grinding composition according to any one of [1] to [6] above has a pH of 7 or higher and 14 or lower.

[0128] [8] The grinding composition according to any one of [1] to [7] above is used for grinding a grinding object containing resin material.

[0129] [9] The grinding composition according to [8] above, wherein the resin material comprises polyimide.

[0130]

[10] The grinding composition according to [8] or [9] above, wherein the grinding object further comprises a metallic material.

[0131]

[11] The grinding composition according to any one of [1] to

[10] above is substantially free of chelating agents.

[0132]

[12] A grinding method comprising a step of grinding an object to be ground using the grinding composition described in any one of [1] to

[11] above.

[0133] Example

[0134] Embodiments of this disclosure will be described. However, the technical scope of this disclosure is not limited to the following embodiments. It should be noted that, unless otherwise specified, "%" and "parts" refer to "mass %" and "parts by mass," respectively. The pH of the grinding composition was measured using a pH meter.

[0135] (Example 1)

[0136] Alumina particles, used as abrasives, were mixed with pure water and then appropriately pulverized and classified. Next, polyoxyethylene decyl ether (average molar number of oxyethylene additions: 7) was added as a surfactant at a final concentration of 0.05% by mass, and benzotriazole was added as a corrosion inhibitor at a final concentration of 0.02% by mass. Then, the pH was adjusted to 10.5 using potassium carbonate as a pH adjuster, yielding grinding composition 1 (mixing temperature: approximately 25°C, mixing time: approximately 30 minutes). The concentration of alumina particles in grinding composition 1 was 3% by mass.

[0137] (Example 2)

[0138] Alumina particles, used as abrasives, were mixed with pure water and then appropriately pulverized and classified. Next, potassium hydroxide was used as a pH adjuster to adjust the pH to 11.5, yielding grinding composition 2 (mixing temperature: approximately 25°C, mixing time: approximately 30 minutes). The concentration of alumina particles in grinding composition 2 was 5% by mass.

[0139] (Example 3)

[0140] Without using potassium hydroxide as a pH adjuster, the process was otherwise identical to that in Example 2 to obtain grinding composition 3 (mixing temperature: approximately 25°C, mixing time: approximately 30 minutes). The concentration of alumina particles in grinding composition 3 was 5% by mass, and the pH value of grinding composition 3 was 7.0.

[0141] (Comparative Examples 1-4)

[0142] Alumina particles, used as abrasives, were mixed with pure water and then appropriately pulverized and classified. This yielded comparative compositions 1 to 4 for grinding.

[0143] The physical properties of the alumina particles contained in the above-obtained polishing composition, the polishing removal rate when polishing a polyimide substrate using the polishing composition, and the scratches on the surface of the polished polyimide substrate were evaluated.

[0144] [evaluate]

[0145] <Peaks of alumina particles>

[0146] The particle size distribution of alumina particles was measured using a laser diffraction particle size analyzer (Microtrac BEL Co., Ltd., Microtrac Particle Size Analyzer MT3300EX II) to determine the volumetric particle size distribution. In cases where the obtained particle size distribution is bimodal, the peak on the smaller particle size side was designated as the first peak, and the peak closer to the larger particle size side was designated as the second peak. The particle size PS1 at the apex of the first peak, the peak height H1 of the first peak, the particle size PS2 at the apex of the second peak, and the peak height H2 of the second peak were determined. It should be noted that the volumetric particle size distribution of the alumina particles contained in the grinding compositions in Comparisons 1 to 4 is unimodal.

[0147] D2, D of alumina particles 50 D 98 >

[0148] In the volume-based particle size distribution of the alumina particles obtained above, the particle size with a cumulative frequency of 2% from the smallest particle size side is defined as D2 of the alumina particles, and the particle size with a cumulative frequency of 50% from the smallest particle size side is defined as D3 of the alumina particles. 50 The particle size with a cumulative frequency of 98% from the smallest particle size side is defined as the D of the alumina particle. 98 .

[0149] <BET specific surface area of ​​alumina particles>

[0150] The BET specific surface area (SA) of alumina particles was measured using a fully automated specific surface area measuring device (Macsorb HM model-1201, registered trademark) manufactured by Mounttech Co., Ltd.

[0151] <Theoretical specific surface area SA' of alumina particles>

[0152] The theoretical specific surface area SA' of alumina particles was determined using the D measured above. 50 The value of is calculated using the following formula (5).

[0153]

[0154] In the above formula (5), ρ is the density of alumina particles, which is 3.95 g / cm³. 3 The value of .

[0155] Based on the above, D2 and D 50 D 98 SA and SA' are used to calculate the irregularity N and skewness S according to the following formulas (1) and (3).

[0156]

[0157]

[0158] <Evaluation of grinding removal speed and scratches>

[0159] A polyimide (PI) substrate was prepared as the object to be polished. Using various polishing compositions, the object was polished under the polishing apparatus and conditions described below. The polishing removal rate of the polyimide was evaluated according to the method described below (polishing removal rate evaluation method), and the scratches on the surface of the polished polyimide substrate were evaluated according to the method described below (scratch evaluation method).

[0160] (Object to be ground)

[0161] Polyimide substrate: Size: 30mm × 30mm (manufactured by Asahi Kasei Corporation, trade name PIMEL BL301).

[0162] (Grinding apparatus and grinding conditions)

[0163] Grinding device: Small benchtop grinder (EJ380IN, manufactured by Engis Co., Ltd., Japan)

[0164] Plate diameter: 380 mm

[0165] Abrasive pad: Non-woven fabric pad (FP4 manufactured by Fujibo Ehime Co., Ltd.)

[0166] Pressure plate (flat plate) rotation speed: 50 rpm

[0167] Grinding head (carrier) rotation speed: 50 rpm

[0168] Grinding pressure: 3.9 psi (274 g / cm³) 2 ]、270kPa)

[0169] Flow rate of the grinding composition: 80 ml / min

[0170] Grinding time: 1 min.

[0171] (Method for evaluating grinding removal rate)

[0172] 1. Using an analytical balance XS205 (manufactured by Mettler-Toledo Co., Ltd.), the mass of the object to be ground before and after grinding was determined, and the change in mass of the object to be ground before and after grinding, ΔM [kg], was calculated from the difference between them;

[0173] 2. Divide the change in mass of the object being ground, ΔM [kg], by the specific gravity of the object being ground (the specific gravity of the material being ground), and calculate the change in volume of the object being ground, ΔV [m]. 3 ];

[0174] 3. The volume change ΔV[m] of the object to be ground before and after grinding. 3 Divide by the area s[m] of the grinding surface of the object being ground. 2 From this, the change in thickness Δd[m] of the object to be ground before and after grinding can be calculated;

[0175] 4. Divide the thickness change Δd [m] of the workpiece before and after grinding by the grinding time t [min], and then convert the unit to [µm / min]. Use this value as the grinding removal rate v [µm / min].

[0176] (Methods for evaluating scratches)

[0177] Visually inspect the surface of the polished polyimide substrate and evaluate the scratches according to the following evaluation criteria;

[0178] 〇: Under fluorescent light, the scratches cannot be confirmed by visual inspection.

[0179] ×: The scratches can be visually confirmed under fluorescent light.

[0180] The physical properties of the alumina particles contained in the grinding composition are shown in Table 1 below, and the composition and evaluation results of the grinding composition are shown in Table 2 below. It should be noted that "-" in Table 2 below indicates that the component was not used.

[0181] [Table 1]

[0182]

[0183] [Table 2]

[0184]

[0185] As can be seen from Table 2 above, the polyimide in the polishing composition of the Examples exhibits a high polishing removal rate, and the scratches on the surface of the polished polyimide substrate are also reduced. On the other hand, it can be seen that either the polishing removal rate of the polyimide in the Polishing Composition of the Comparative Examples or the number of scratches on the surface of the polished polyimide substrate is worse than that of the Examples.

[0186] This application is based on Japanese Patent Application No. 2025-055779, filed on March 28, 2025, the disclosure of which is incorporated herein by reference in its entirety.

Claims

1. A grinding composition comprising: Water, and Alumina particles, The volumetric particle size distribution of the alumina particles exhibits a bimodal distribution.

2. The grinding composition according to claim 1, wherein, In the volume-based particle size distribution of the alumina particles, The peak on the smaller particle size side is set as the first peak. When the peak that is closer to the larger particle size side than the first peak is designated as the second peak... The ratio of the particle size PS2 at the peak of the second peak to the particle size PS1 at the peak of the first peak, PS2 / PS1, is greater than 1.3 and less than 3.

3. The grinding composition according to claim 2, wherein, Set the peak height of the first peak to H1. When the peak height of the second peak is set to H2, The ratio H2 / H1 of the peak height of the second peak to the peak height of the first peak is greater than 0.1 and less than 1.

0.

4. The grinding composition according to claim 1, wherein, The BET specific surface area of ​​the alumina particles is set as SA. The particle size distribution based on volume of the alumina particles, with the cumulative frequency from the smallest particle size side being 50% of the particle size, is defined as D. 50 , will be by the D 50 When the calculated theoretical specific surface area is set as SA', The irregularity N shown in equation (1) satisfies the relationship in equation (2). 。 5. The grinding composition according to claim 4, wherein, In the volume-based particle size distribution of the alumina particles, Let the cumulative frequency from the smallest particle size side be 2% of the particle size, and set that as D2. Let the particle size from the smallest particle size side, where the cumulative frequency is 98%, be defined as D. 98 hour, The skewness S shown in equation (3) below satisfies the relationship in equation (4) below. 。 6. The grinding composition according to claim 4, wherein, The D of the alumina particles 50 It is above 0.5µm and below 0.9µm.

7. The grinding composition according to claim 1, wherein the pH is 7 or higher and 14 or lower.

8. The grinding composition according to claim 1, used for grinding a grinding object containing resin material.

9. The grinding composition according to claim 8, wherein, The resin material contains polyimide.

10. The grinding composition according to claim 8, wherein, The object to be ground also includes metallic materials.

11. The grinding composition according to claim 1, which substantially does not contain a chelating agent.

12. A grinding method comprising the step of grinding an object to be ground using the grinding composition of claim 1.

Citation Information

Patent Citations

  • Abrasive composition

    JP2005268666A

  • System

    JP2025055779A

  • Polishing composition and polishing method

    US20050204638A1